PENGARUH PERCEIVED USEFULNESS, PERCEIVED RISK DAN PERCEIVED EASE OF USE TERHADAP INTEREST ONLINE PURCHASE YANG DIMEDIASI CONSUMER ATTITUDE PADA APLIKASI DEALJAVA DI SURABAYA - Prayogo, Cornelia; Ellitan, Lena; Muljani, Ninuk (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2021)
Due to the rapid growth of technology, especially the Internet,business people take advantage of the development of internet usersby creating trading businesses in the form of electronic stores. Variouse-commerce apps emerge, which do not only sell products but alsoservices by using numerous application programs for variouspurposes. One example of an application-based business service is theDealjava. Various applications are managed properly starting fromperceived usefulness, perceived risk, and perceived ease of use, whichwill give an impact on consumer attitude and interest in onlinepurchases. This study aims to analyze the perceived usefulness,perceived risk, and perceived ease of use to the interest onlinepurchase, whether in a direct way or through consumer attitude in theDealjava Apps in Surabaya. The object of this study was the users ofthe Dealjava application aged more than 17 years old in Surabaya.There were 141 samples of study that used Partial Least Techniquesquare. The data used was primary data that was obtained bydistributing questionnaires to the Dealjava users in Surabaya.Structural Equation Modeling with SmartPLS software was used asa data analysis technique. The result of the study proves that theperceived usefulness, perceived risk, perceived ease of usesignificantly affect consumer attitude; perceived usefulness, perceivedrisk, perceived ease of use, and consumer attitude automaticallyaffect the interest in online purchase; perceived risk and perceived easeof use undoubtedly affect the interest online purchase throughconsumer attitude; perceived usefulness does not have a significanteffect on interest online purchases through consumer attitude.